Mild hypoglycemia is independently associated with increased risk of mortality in patients with sepsis: a 3-year retrospective observational study - Park, Sunghoon (BioMed Central, 2012)
INTRODUCTION: Mild hypoglycemia is associated with increased mortality in critically ill patients. However, data regarding the association between mild hypoglycemia and patient outcomes among patients with sepsis are limited. METHODS: Patients admitted to a medical ICU for sepsis, as defined by the Surviving Sepsis Campaign guidelines, during a 3-year period were enrolled retrospectively. Data on blood glucose (BG) control parameters and patient outcomes were collected. The primary outcome was the relationship of mild hypoglycemia (defined as minimum BG of 40 to 69 mg/dl during ICU stay) to hospital mortality, and the secondary outcomes were ICU-acquired complication rates, ICU and 1-year mortality rates. A relationship between glucose variability and hypoglycemic events was also investigated. RESULTS: Three-hundred and thirteen consecutive patients with sepsis were enrolled (mean age, 71.8 ± 11.3 years; male, n = 166; diabetics, n = 102). A total of 14,249 (5.6/day/patient) BG tests were performed, and 175 hypoglycemic events (spontaneous, n = 71; iatrogenic, n = 104) occurred in 80 (25.6%) patients during the ICU stay; severe hypoglycemia (minimum BG level < 40 mg/dl) occurred in 24 (7.7%) patients, and mild hypoglycemia (minimum BG level 40 to 69 mg/dl) was found in 56 (17.9%) patients. The frequency of hypoglycemic events increased with higher glucose variability, and patients with mild hypoglycemia had higher rates of ICU-acquired complications than did those with no hypoglycemia (renal, 36.2% vs. 15.6%, P = 0.003; cardiac, 31.9% vs. 14.3%, P = 0.008; hepatic, 34.0% vs. 18.2%, P = 0.024; bacteremia, 14.9% vs. 4.5%, P = 0.021). Multivariate analysis revealed that mild hypoglycemia was independently associated with increased hospital mortality (odds ratio, 3.43; 95% confidence interval, 1.51 to 7.82), and even a single event was an independent risk factor (odds ratio, 2.98; 95% confidence interval, 1.10 to 8.09). Kaplan-Meier analysis demonstrated that mild hypoglycemia was significantly associated with a lower 1-year cumulative survival rate among patients with sepsis (P < 0.001). CONCLUSION: Mild hypoglycemia was associated with increased risk of hospital and 1-year mortality, as well as the occurrence of ICU-acquired complications. Physicians thus need to recognize the importance of mild hypoglycemia in patients with sepsis.